2008
DOI: 10.1021/jf800980w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Wood Pretreatments on the Sorption−Desorption of Linuron and Metalaxyl by Woods

Abstract: The sorption-desorption of two different pesticides, linuron and metalaxyl, by woods was studied. Sorbent/solution ratio and sorption kinetics were also determined. Untreated wood and water, NaOH, HCl, and octadecyltrimethylammonium bromide (ODTMA) treated pine (softwood) and oak (hardwood) were used as sorbents. Linuron and metalaxyl were sorbed by untreated woods up to 80 and 40%, respectively, in a short time when the sorbent/solution ratio of 1:10 was used. Sorption of pesticides was significantly higher b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 36 publications
0
8
1
1
Order By: Relevance
“…Recent literature reports several studies on the effective adsorption of many organic compounds such as pesticides [153,154,271,[282][283][284][285][286][287][288][289], phenolic compounds [290][291][292][293][294][295], dyes [144,[296][297][298][299][300][301], PAHs [302,303], explosives [304] and pharmaceuticals and hormonal compounds [85,[305][306][307] by a variety of adsorbents prepared from agricultural wastes. The list of materials that have been tested in such studies is long (and still increasing).…”
Section: Industrial and Agricultural Wastes And By-productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature reports several studies on the effective adsorption of many organic compounds such as pesticides [153,154,271,[282][283][284][285][286][287][288][289], phenolic compounds [290][291][292][293][294][295], dyes [144,[296][297][298][299][300][301], PAHs [302,303], explosives [304] and pharmaceuticals and hormonal compounds [85,[305][306][307] by a variety of adsorbents prepared from agricultural wastes. The list of materials that have been tested in such studies is long (and still increasing).…”
Section: Industrial and Agricultural Wastes And By-productsmentioning
confidence: 99%
“…The list of materials that have been tested in such studies is long (and still increasing). Some examples include pine bark [282,283,302,304,305], almond shells [292,307], banana peels [284,293], sawdust [153,285,300], coconut fibers [285], rice bran [271,287], rice husk [271,287], moringa pods [271], hazelnut shells [299,300], wood residues [286], cork wastes [85,153,154,289,295,303,306] and chickpea husk [288]. In addition, assays have also been conducted with some of these materials after submitting them to more or less complex treatments (usually thermal), e.g.…”
Section: Industrial and Agricultural Wastes And By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining the data of pesticides with a wider range of K ow (3–1.61) and solubility (81–8400 mg L −1 ) from Torrents et al (1997) and from our study, we obtained a model for the prediction of K foc according to the following equation: log Kfoc=(2.76±0.29)+(0.53±0.09) log Kow(2.97±0.22) PIThe r 2 coefficient explained 90% of the variability of K foc and hardly increased when the solubility was included as a variable for the model, as reported by Torrents et al (1997) Validation of this model with data of linuron and metalaxyl sorption by untreated and treated woods with different PI (Rodríguez‐Cruz et al, 2008) revealed a significant correlation ( r = 0.83; p < 0.001) and pointed out that the application of this equation to real wood data should be further explored.…”
Section: Resultsmentioning
confidence: 86%
“…Industrially, paper and pulp wastewater are treated with QAC-functionalized molecular sieves to remove dyes [4]; waters contaminated with pesticides (i.e. linuron) are cleaned via sorption to QAC treated wood [8] or sorption to QAC treated soils [9]. Anticholinergic drugs also utilize QACs as active ingredients [10].…”
Section: Introductionmentioning
confidence: 99%